MELTING OF LUMP MATERIAL IN IRON-CARBON MELT IN THE PROCESS OF MELTING IN BLAST STEEL FURNACE - V. I. Timoshpolskij; S. V. Korneev (Литьë и металлургия, 2007)
The mechanism of the lump metal scrap melting at loading it into liquid melt is investigated.